Middle-range nursing theory for mental health care (Research, Society and Development, 2020)
To describe the elements of a nursing theory in mental health, oriented towards proposing a focus of nursing action in mental health in the context of the Psychosocial Care Center for Alcohol Other Drugs. Theoretical study for the conceptualizing a middle-range theory produced from the theoretical combination strategy of the Conceptual Model and the King's Theory of Goal Attainment and the Brazilian Unified Health System model care. Was produced the synthesis Vee correlating disciplinary elements of nursing with the conceptual and philosophical issues of Unified Health System, and the methodological aspects of mental health care. Nine relational statements to the theory were presented. The Middle-Range Nursing Theory for Mental Health Care describes, explains, and contributes to the performance of mental health nursing professionals.